Collagen Gly missense mutations: Effect of residue identity on collagen structure and integrin binding - Qiu, Yimin (J Struct Biol, 2018)
Gly missense mutations in type I collagen, which replace a conserved Gly in the repeating (Gly-Xaa-Yaa)(n) sequence with a larger residue, are known to cause Osteogenesis Imperfecta (OI). The clinical consequences of such mutations range from mild to lethal, with more serious clinical severity associated with larger Gly replacement residues. Here, we investigate the influence of the identity of the residue replacing Gly within and adjacent to the integrin binding (502)GFPGER(507) sequence on triple-helix structure, stability and integrin binding using a recombinant bacterial collagen system. Recombinant collagens were constructed with Gly substituted by Ala, Ser or Val at four positions within the integrin binding region. All constructs formed a stable triple-helix structure with a small decrease in melting temperature. Trypsin was used to probe local disruption of the triple helix, and Gly to Val replacements made the triple helix trypsin sensitive at three of the four sites. Any mutation at Gly505, eliminated integrin binding, while decreased integrin binding affinity was observed in the replacement of Gly residues at Gly502 following the order Val > Ser > Ala. Molecular dynamics simulations indicated that all Gly replacements led to transient disruption of triple-helix interchain hydrogen bonds in the region of the Gly replacement. These computational and experimental results lend insight into the complex molecular basis of the varying clinical severity of OI.